A Combined MPC and PI Control Strategy for Bidirectional Interleaved Totem Pole PFC Converters in Electric Vehicle G2V and V2G Applications - Lassioui Abdellah; Kabba Abdelaziz; El Ancary Marouane; Hasni Anwar; El Asri Yassine; El Idrissi Zakariae; El Fadil Hassan (E3S Web of Conferences)
This paper presents an optimized control strategy for a bidirectional interleaved totem pole Power Factor Correction (PFC) converter, employing a combination of Model Predictive Control (MPC) and a Proportional-Integral (PI) controller. The converter’s mathematical model is used to implement the MPC, which ensures a unit power factor during both Grid-to-Vehicle (G2V) and Vehicle-to-Grid (V2G) operations. Meanwhile, the PI controller regulates the DC-side voltage. It is worth noting that the MPC’s design eliminates the need for a comparator to generate the Pulse Width Modulation (PWM) signal, simplifying the control architecture. The proposed control technique’s effectiveness is validated through various simulation scenarios in both G2V and V2G power transfer modes, demonstrating satisfactory performance. This integrated approach provides a robust solution for efficient energy management and high-quality power conversion in bidirectional PFC converters.